The Research of the Need for Occupational Therapy in the Infant`s Foster Home - Viktorija Repšaitė; Giedrė Kavaliauskienė; Ligija Švedienė (Lithuanian Sports University, 2020)
The aim of the research was to examine the need for occupational therapy in the infant foster home. The study was conducted in December 2009 - March 2010 in Kaunas Child's Development Clinic "Lopšelis". Self-dependence and fine motor function evaluation were made according to DISC (Diagnostic Inventory for Screening Children). Sensory integration disorders were valuated by the questionnaire of evaluation of sensory integration filled in by the teachers (for children from birth to 2 years) which helped the teachers to evaluate the babies growing in the foster home. Evaluating fine motor skills we estimated that 22 children (57.9%) were of normal development, 13 children (34.2%) had development retardation and 3 children (7.9%) had development difficulties. Evaluating the self-dependence of the children growing in the infant foster home, we determined that 25 children (65.8%) were of normal development, 12 children (31.6%) had development retardation and 1 child (2.6%) had development difficulties. Both child's self-dependence and fine motor skills depend on the age (varies with the growth of a child). To assess the influence of the changes in living conditions on child's development regardless of age, we created a new character - children's part time (in percent) spent in infant foster homes. The results of the research revealed that the longer a child lives in a foster home, the more their self-dependence and fine motor skills weaken. The results of the questionnaire for assessment of sensory integration disorders were analyzed and total score of 9 areas was counted. It varied from 55 to 95 points, the average of the total score was 76.2 points. The correlation coefficient between sensory integration disorder (total score) and the time children spent in the infant foster home was r = 0.35, p = 0.08. Therefore, it can be stated with the 90 % reliability that the longer a child lived in a foster home, the more pronounced his / her sensory integration disorders were. Conclusions. 1. A large proportion of infants (20 (42.1%)) growing in the infant foster home have fine motor function development disorders: 13 children (34.2%) were stated to have fine motor development retardation, 3 children (7.9%) had development difficulties. 2. Infants growing in a foster home have disorders of the development of self-dependence skills. We found that 12 children (31.6%) had characteristic retardation of self-dependence skills development, and 1 child (2.6%) had development disorders. 3. Infants growing in the infant foster home have sensory integration disorders. The results of the research showed that 9 (35%) of the respondents had light sensory integration disorders, 10 (38%) respondents had medium sensory integration disorders and 1 (4%) respondent had pronounced sensory integration disorder. Keywords: occupational therapy, developmental disorders, foster homes.